2008
DOI: 10.1128/mcb.01500-07
|View full text |Cite
|
Sign up to set email alerts
|

SLIP1, a Factor Required for Activation of Histone mRNA Translation by the Stem-Loop Binding Protein

Abstract: Replication-dependent histone mRNAs are the only eukaryotic cellular mRNAs that are not polyadenylated, ending instead in a conserved stem-loop. The 3 end of histone mRNA is required for histone mRNA translation, as is the stem-loop binding protein (SLBP), which binds the 3 end of histone mRNA. We have identified five conserved residues in a 15-amino-acid region in the amino-terminal portion of SLBP, each of which is required for translation. Using a yeast two-hybrid screen, we identified a novel protein, SLBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 40 publications
3
99
1
Order By: Relevance
“…It has been reported previously that MIF4GD interacts with SLBP and is required for efficient translation of histone mRNAs (Cakmakci et al 2008). Because INT6 is associated with the eIF3 translation initiation complex and binds MIF4GD, we next examined whether INT6 is also important for histone mRNA translation.…”
Section: Int6 Is Necessary For Efficient Translation Of Histone Mrnasmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported previously that MIF4GD interacts with SLBP and is required for efficient translation of histone mRNAs (Cakmakci et al 2008). Because INT6 is associated with the eIF3 translation initiation complex and binds MIF4GD, we next examined whether INT6 is also important for histone mRNA translation.…”
Section: Int6 Is Necessary For Efficient Translation Of Histone Mrnasmentioning
confidence: 99%
“…Besides its role in formation of the 39 end, SLBP is also important for export of the histone mRNA (Ghule et al 2008;Sullivan et al 2009a), as well as for their productive translation, and this translational activity relies on interactions with eIF4G and eIF3 translation initiation factors (Ling et al 2002;Gorgoni et al 2005). More recently, it has also been reported that this effect involves an interaction with a protein identified in a two-hybrid screen performed with SLBP as bait, which was accordingly named SLBP interacting protein 1 (SLIP1) (Cakmakci et al 2008). This small 25-kDa protein corresponds almost entirely to a middle domain of eukaryotic initiation factor 4G (MIF4G) and has been designated accordingly as MIF4G domain-containing protein (MIF4GD) by the HUGO Gene Nomenclature Committee, which name is further used in this article.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Lsm4 showed the most robust binding, we focused only on it for this study. We also tested the ability of the seven Lsm proteins to interact with GST-SLIP1, a component of the cytoplasmic histone mRNP that is involved in translation (Cakmakci et al 2008). None of the subunits of the Lsm1-7 complex interacted directly with SLIP1 (Supplemental Data).…”
Section: Lsm4 Interacts Directly With the Rna Binding Domain Of Slbpmentioning
confidence: 99%